1981
DOI: 10.1055/s-2007-971689
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and Chemical Investigation of Thyme Liquid Extracts

Abstract: Thymks vulgaris L. and Thymus ser-py1lun L. are used as antitussive remedies. Liquid thyme extracts have been studied in vitro for spasmolytic activity on the smooth muscles of the guinea-pig trachea and ileum. Treatment of the carbachol induced tracheal strip with thyme extracts resulted in relaxation of this preparation. Ileum contractions due to acetyicholine, were reduced in the same proportion. Thymol and carvacro! content was determined with HPLC. Phenol concentration of examined extracts was very low ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

1988
1988
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 7 publications
(10 reference statements)
2
28
0
2
Order By: Relevance
“…Although these compounds have been shown to prevent contractions induced in the ileum and the trachea of the guinea-pig, by histamine, acetylcholine and other reagents, the concentration of phenolics in aqueous preparations of the drug is insufficient to account for this activity (Van Den Broucke, 1980;Van Den Broucke and Lemli, 1981). Our previous study (Boskabady and Jandaghi, 2003) showed a potent effect for carvacol, which is one constituent of Thymus vulgaris.…”
Section: Discussionmentioning
confidence: 96%
“…Although these compounds have been shown to prevent contractions induced in the ileum and the trachea of the guinea-pig, by histamine, acetylcholine and other reagents, the concentration of phenolics in aqueous preparations of the drug is insufficient to account for this activity (Van Den Broucke, 1980;Van Den Broucke and Lemli, 1981). Our previous study (Boskabady and Jandaghi, 2003) showed a potent effect for carvacol, which is one constituent of Thymus vulgaris.…”
Section: Discussionmentioning
confidence: 96%
“…In some countries thyme liquid extracts are a fundamental component of many galenic preparations and drugs with antitussive activity . Van den Broucke and Lemli (1981) found that thymol and carvacrol cannot induce the spasmolytic activity of thyme liquid extracts because their concentration is too low ( ~ 0.0 I%). Some extracts showed high spasmolytic action, but no correlation between phenol content and activity was observed.…”
Section: The Use Of Active Principlesmentioning
confidence: 99%
“…La biodiversité se manifeste donc par un polymorphisme chimique des huiles essentielles. Il en résulte une large gamme d'activités biologiques, antiseptiques, antibactériennes, antifongiques, antispasmodiques et anti-oxydantes pour citer les mieux connues (Van den Broucke & Lemli, 1981 ;Biondi et al, 1993 ;Faleiro et al, 2003).…”
Section: Introductionunclassified